Elimination of dyes from aqueous solutions using iron oxides and chitosan as adsorbents: a comparative study - Silvina Pirillo; Viviana Pedroni; Elsa Rueda; María Luján Ferreira (Química Nova, 2009)
This work investigates the adsorption of Alizarin, Eriochrome Blue Black R and Fluorescein using chitosan, goethite and magnetite as adsorbents. For Alizarin, the best adsorbent is chitosan with a Langmuir parameter of 15.8 mmol dye/g adsorbent. For Eriochrome Blue Black R only 1.94 mmol dye/g chitosan is adsorbed. Langmuir parameters for the Alizarin adsorption on both iron oxides display one or two orders of magnitude lower than for chitosan and two orders of magnitude lower in the case of Eriochrome Blue Black R. Fluorescein does not adsorb in appreciable amounts on chitosan and it presents the lower affinity on the iron oxides.